Drug-eluting stents vs. bare metal stents in patients with cardiogenic shock. Issue 3 (March 2015) - Jaguszewski, Milosz; Ghadri, Jelena-Rima; Seifert, Burkhardt; Hiestand, Thierry; Herrera, Paola; Gaemperli, Oliver; Landmesser, Ulf; Maier, Willibald; Nallamothu, Brahmajee K.; Windecker, Stephan; Lüscher, Thomas F.; Templin, Christian
<x xml:space="preserve">Abstract</x> Background In patients with cardiogenic shock, data on the comparative safety and efficacy of drug-eluting stents (DESs) vs. bare metal stents (BMSs) are lacking. We sought to assess the performance of DESs compared with BMSs among patients with cardiogenic shock undergoing percutaneous coronary intervention (PCI). Methods Out of 236 patients with acute coronary syndromes complicated by cardiogenic shock, 203 were included in the final analysis. The primary endpoint included death, and the secondary endpoint of major adverse cardiac and cerebrovascular events (MACCEs) included the composite of death, myocardial infarction, any repeat revascularization and stroke. Patients were followed for a minimum of 30 days and up to 4 years. As stent assignment was not random, we performed a propensity score analysis to minimize potential bias. Results Among patients treated with DESs, there was a lower risk of the primary and secondary endpoints compared with BMSs at 30 days (29 vs. 56%, P < 0.001; 34 vs. 58%, P = 0.001, respectively) and during long-term follow-up [hazard ratio 0.43, 95% confidence interval (CI) 0.29–0.65, P < 0.001; hazard ratio 0.49, 95% CI 0.34–0.71, P < 0.001, respectively]. After propensity score adjustment, all-cause mortality was reduced among patients treated with DESs compared with BMSs both at 30 days [adjusted odds ratio (OR) 0.26, 95% CI 0.11–0.62; P = 0.002] and during long-term follow-up (adjusted hazard ratio 0.40, 95% CI 0.22–0.72; P = 0.002). The rate of MACCE was lower among patients treated with DESs compared with those treated with BMSs at 30 days (adjusted OR 0.42, 95% CI 0.19–0.95; P = 0.036). The difference in MACCEs between devices approached significance during long-term follow-up (adjusted hazard ratio 0.60, 95% CI 0.34–1.01; P = 0.052). Conclusion DESs appear to be associated with improved clinical outcomes, including a reduction in all-cause mortality compared with BMSs among patients undergoing PCI for cardiogenic shock, possibly because of a pacification of the infarct-related artery by anti-inflammatory drug. The results of this observational study require confirmation in an appropriately powered randomized trial.